Un mondo precario in bilico tra verità e menzogna - Bianchi, Matteo (Elephant & Castle, 2017)
The essay analyzes the word “post-truth” and its philosophical and political implications with a literary and sociological approach. The analysis focuses on italian political life, where storytelling has become more important than the truth. “Post-truth” is an expression of the philosophical concepts of postmodernism and can be related to the theme to the human body. In a brief review that analyzes policy making from Mussolini and Moro up to Berlusconi and Renzi, the essay shows how the regality of the political body is lost and how only the weak and fragile human body. In this a transition from the embodiment of a political function to the exhibition of the person, the body of the politician is so mediatic that it becomes empty and powerless. As in Alison Jackson’s work, this body seems to live in a glamorous world like the German legend of Hamelin’s piper.